PENGUATAN INTEGRITAS PERADILAN MELALUI PENERAPAN SISTEM KAMAR DI PERADILAN UMUM - Putra, Ilhamdi (Judex Laguens, 2023)
The dynamics of community development have resulted in an increase in legal conflicts arising as factual expressions between legal subjects, as well as influencing an increase in cases in court. Meanwhile, the General Court does not classify the Panel of Judges based on areas of expertise, between criminal and civil cases, which has the potential to disrupt the integrity of the judiciary. This phenomenon boils down to two issues, namely the urgency of classifying the fields of expertise of judges in the General Courts in terms of the public character of criminal cases and the private character of civil cases, as well as the workload of judges and the design of the chamber system within the General Courts. This study concludes that the absence of a judge's expertise in the General Courts greatly affects the integrity of the judiciary. This happened due to the mixing of judges with a variety of cases of a different nature, between public and private. This phenomenon necessitates the application of a chamber system in the General Courts through the Criminal Chamber and the Civil Chamber in the District Court and High Court. This design which focuses on the judges' areas of expertise is in line with the model for filling the positions of Candidates for Supreme Court Justices which go directly to the Chamber System through areas of expertise. Keyword: Integrity, Chamber System, General Judiciary